A Comparative Analysis of the Socioeconomic Dimensions of LGBTI Exclusion in Serbia - World Bank Group (World Bank, Washington, DC, 2019)
The study uses the survey on income and living conditions (SILC) to collect data on income, poverty, social exclusion, and living conditions of lesbian, gay, bisexual, transgender, and intersex (LGBTI) people in Serbia, allowing a robust comparison between the socioeconomic outcomes of sexual and gender minorities and the general population.